Імпульсні градієнтні системи - Шарко, Ю.В. (Інститут математики НАН України, 2006)
В роботi розглядається система диференцiальних рiвнянь з iмпульсною дiєю побудована в областi евклiдового простору Rⁿ . В ходi дослiдження якiсної поведiнки iнтегральних кривих цiєї системи приводиться критерiй iснування замкнених орбiт i умова iснування їх орбiтальної стiйкостi. Investigate system of differential equations with impulse action. Gradient system of differential equations is considered in domain of Euclidean space Rⁿ. By the investigation of the qualitative behaviour of integral curves of this system is given the criterion of existence of closed orbits and the condition of their orbital stability.